2018
DOI: 10.1016/j.rmed.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the content and delivery of education in pulmonary rehabilitation programmes

Abstract: Introduction: Pulmonary rehabilitation (PR) is a core component of Chronic Obstructive Pulmonary Disease (COPD) management with well recognized benefits. While suggestions for educational content within pulmonary rehabilitation have been detailed in clinical guidance, it is unclear what educational content is delivered as part of pulmonary rehabilitation, who delivers it, and how it is delivered.Methods: A systematic review was conducted to identify what educational content is delivered as part of pulmonary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Our previous systematic review showed that in the published literature several topics were not featured and there were few tools used to evaluate the effectiveness of education. 22 This cross-sectional survey provides data on 64% of the PR sites across Scotland (response rate of 81.8%, 9/11 respondents), includes data from 17 PR teams across Scotland. This survey set out to examine what is delivered in practice, it is the first to show in detail what educational content is delivered and who is involved in the teams and delivery of education within PR across Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous systematic review showed that in the published literature several topics were not featured and there were few tools used to evaluate the effectiveness of education. 22 This cross-sectional survey provides data on 64% of the PR sites across Scotland (response rate of 81.8%, 9/11 respondents), includes data from 17 PR teams across Scotland. This survey set out to examine what is delivered in practice, it is the first to show in detail what educational content is delivered and who is involved in the teams and delivery of education within PR across Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…82 As PR includes exercise training under the direction of a health-care professional, this may address exertional breathlessness-related cognitive and emotional factors, even when CBT is not intentionally prescribed. There is significant overlap in components of CBT interventions listed in the included studies (eg,education on anxiety and COPD; education about depression and inactivity in COPD; distraction, relaxation, and breathing techniques; self-monitoring and goal setting) and common content of the education component of pulmonary rehabilitation (anxiety/depression and panic control management; symptom management including breathing strategies 83 ). In both center-or home-based PR programs, 84 individualized education and goal setting occurs during the supervised exercise sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Six sessions will be conducted by a multidisciplinary team. Based on the literature and previous experience, it is anticipated that some themes will need to be addressed [42, 81–84] however, the component will be tailored to patients and caregivers’ needs. A detailed description of these sessions can be found in Fig.…”
Section: Methodsmentioning
confidence: 99%